(untitled) (Journal of Business and Technology (Dhaka), 2015)
This paper examines the profitability and consistency of the second leading export oriented industry of Bangladesh. The secondary data of the five leading companies namely, Fu-Wang, Monno, Shinepukur, Standard and RAK Ceramics are collected from the annual reports of 2006-2012 from their websites. The collected data are processed and analyzed by SPSS 19 to make interpretations by ANOVA outputs. Different financial tools like Gross profit margin, Operating profit margin, Net profit margin, Return on assets, Return on equity are calculated along with the liquidity ratios and turnover ratios to find out the causes of unexpected results, if any. The researchers find that two of the five companies (Standard and Monno) are performing very poorly, one (Fu-Wang) is performing moderate level and other two (RAK and Shinepukur) are performing comparatively better. The asset and sales management of the poor performers are to be improved immediately, the liquidity position of all the companies is to be improved and the capital structure of Shinepukur is to be reconstructed. Journal of Business and Technology (Dhaka) Vol.9(2) 2014; 1-13